bell hooks e a Trilogia do Ensino: contribuições para uma educação infantil antirracista - Amaral, Elisa Amanda Santos do (2023)
This research addresses the contribution of the word Trilogy Teaching, by bell hooks, for early childhood education from anti-racist perspective. Our research object is composed of the books "TeachingtoTransgress: education as a practice of freedom" (2013), "Teaching community: a pedagogy of Hope" (2021) and "Teaching critical thinking: practical wisdom" (2020). The research has a sits theoretical and methodological basis the Sociology Childhood (SARMENTO, 2008; ABRAMOWICZ, OLIVEIRA, 2010), articulated to the fields of studies of the education of ethnic-racial relations and Black Feminism (COLLINS, 2019; DAVIS, 2016; CRENSHAW, 2002, HOOKS, 2019), which also contributes in order to contextualize the thought of bell hooks. The study seeks to answer whether there are contributions of bell hooks' Teaching Trilogy to early childhood education from anti-racist perspective. This is a qualitative, bibliographic and documental research, in which we conducted a bibliographic survey and analyzed the legislation that guides early childhood education in Brazil. Through the content analysis methodology (Bardin, 2016), we listed ten units of record present in the Trilogy of Teaching that reflect the thought of bell hooks about education and, from them, we chose two, "Eros and eroticism" and "Love", to deepen the discussion in relation to early childhood education from an antiracist perspective. By relating these registration units to the theoretical framework, we can consider that both can support the construction of practices committed to fighting racism and oppression of all kinds in early childhood education. The analysis of the Teaching Trilogy reveals that the writings of bell hooks present relevant contributions for early childhood education from an anti-racist perspective, while Eros carries the meaning of acceptance and consideration to the subjectivity of each student, as well as Love that, as bell hooks evidences, will always move us away from domination.